Exhibiting to Teach: Cultural Pedagogies and the Reconfiguration of the Afro-Brazilian Art Field (1988–2025) (Revista Apotheke, 2026)
This article examines how Black authorship has gradually occupied territory within the Brazilian art scene through a comparative analysis of six major group exhibitions dedicated to Afro-Brazilian art between 1988 and 2025. Taking A Mão Afro-Brasileira (1988) as a founding landmark, the study investigates transformations in the field by means of a structured database including artists’ gender, year of birth, state of origin, and educational background. The central conceptual framework is that of cultural pedagogy (Andrade; Costa), understood as the set of practices and cultural artifacts that produce learning processes, values, and imaginaries beyond formal schooling. From this perspective, exhibitions and catalogues function as formative devices that teach ways of seeing, interpreting, and narrating Black presence within Brazilian art history. The analysis also draws on Pierre Bourdieu’s notion of the artistic field as a space of symbolic dispute, as well as on authors such as Linda Nochlin and Sueli Carneiro in addressing racial and gender inequalities. The findings identify three curatorial tendencies—historical-genealogical, modern transition, and strongly contemporary—revealing territorial expansion, gender diversification, and academic consolidation. The study concludes that these exhibitions pedagogically reconfigure the criteria of legitimacy and memory structuring the Brazilian art system.
Keywords: Afro-Brazilian Art; Cultural Pedagogy; Exhibitions